27 Henry II, art. 3 (1181). - (:unkn) unknown (My University)
Required all freemen to be armed with a doublet of mail, a head-piece of iron, and a lance. Let all freemen holding chattels to the value of 16 marks to have a hauberk, helmet, a shield, and lance.
Keywords: REQUIRED POSSESSION